2020
DOI: 10.3390/ncrna6010010
|View full text |Cite
|
Sign up to set email alerts
|

ncRNAs in Type-2 Immunity

Abstract: Immunological diseases, including asthma, autoimmunity and immunodeficiencies, affect a growing percentage of the population with significant unmet medical needs. As we slowly untangle and better appreciate these complex genetic and environment-influenced diseases, new therapeutically targetable pathways are emerging. Non-coding RNA species, which regulate epigenetic, transcriptional and translational responses are critical regulators of immune cell development, differentiation and effector function, and may r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 208 publications
(284 reference statements)
0
10
0
Order By: Relevance
“…We discovered 16 miRNAs to be differently expressed in CD4 + CLA + T cells from AD patients (Fig. 3 ) , all except for miR-21 previously undescribed in AD 12 . The magnitude of the expression differences between patients and controls was small, but the effect sizes for miRNA variation are unknown.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We discovered 16 miRNAs to be differently expressed in CD4 + CLA + T cells from AD patients (Fig. 3 ) , all except for miR-21 previously undescribed in AD 12 . The magnitude of the expression differences between patients and controls was small, but the effect sizes for miRNA variation are unknown.…”
Section: Discussionmentioning
confidence: 88%
“…DNA methylation differences have also been detected in the epidermis of AD patients 11 . Altered expression of microRNAs has also shown to play a crucial role in type 2 immunity and in promoting pathogenic mechanisms in AD 12 15 . However, very few studies have analyzed these epigenetic signatures in purified immune cells from AD patients 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that lncRNAs have the function of sponging miRNA and play an important role in lung diseases such as chronic obstructive pulmonary disease, cancer, and asthma (19). LncRNAs regulate epigenetic, transcriptional, and translational responses, and are critical regulators of immune cell differentiation, especially for type-2 immune responses (20,21). Previous studies have suggested that lncRNA TUG1 participates in the development of cancers (22,23), hypoxic pulmonary hypertension (24), and Alzheimer's disease (25).…”
Section: Discussionmentioning
confidence: 99%
“…For further details on the structural classification of lncRNAs, reviews from Dhanoa et al (2018); Zhang et al (2018), andMarchese et al (2017) are excellent resources. That said, lncRNAs are usually transcribed by the RNA polymerase II (Pol II)-dependent process which involves splicing, capping, and poly-adenylation (Bensaoud et al, 2019;Guidi et al, 2020) similarly to mRNA transcription (Marchese et al, 2017). Also, the transcription of lncRNAs is characteristically marked with sequence of initiation, elongation, and termination.…”
Section: Lncrnas: Diversity Transcription and Localizationmentioning
confidence: 99%